PEMBATALAN HIBAH DAN AKIBAT HUKUMNYA TERHADAP SERTIPIKAT HASIL PERALIHAN HAK - AHMAD BUDINTA RANGKUTI (PREMISE LAW JURNAL, 2015)
On the cancellation of the transfer of right in the form of a grant due to the claim made by the heir thinking that his/her legitieme portie has been violated, the legitimaris should claim for the fulfillment of the legitieme portie they deserve as regulated in the stipulation of Article 913 and Article 914 of the Indonesian Civil Codes, not to claim for the cancellation of the transfer of the right to land violating the legitieme portie. Legal consequence of the cancellation of the transfer of ownership of right to granted land occured at Medan State Court through the Decision No: 506/Pdt.G/2008/PN-Mdn in connection with the Decision of Medan High Court No: 297/PDT/2009/PT.MDN, and the Decision of the Supreme Court of Republic of Indonesia No: 2711 KJPdt/2010 stating among other things that the Grant Certificate No: 180/2002 dated August 19, 2002 was invalid and canceled for the sake of Law because the process of its transfer is illegal, therefore the ownership of right to land in accordance with the Certificate of Ownership No: 254/Sei Sikambing-B is returned to the grant giver, Herminder Singh. Legal protection for the certificate holder attached to the revoked certificate of right to the granted land as a strong evidence as guaranted by the stipulation of Article 19 paragraph (2) c of Law No. 5/1960 on Basic Regulation of Agrarian Principle, therefore the plaintiff must be able to prove the existence of the procedural mistakes in the provision of will of grant from Herminder Singh to Rahul. Keywords: Grant, Legitieme Portie, Grant Cancelation.